Chitosan-pectin multilayer coating with anthocyanin grape dye as pH indicating wound dressing: Synthesis and characterization - Jovana Petkovska; Nikola Geskovski; Darka Marković; Vesna Dimova; Dejan Mirakovski; Maja Radetić; Igor Jordanov (Carbohydrate Polymer Technologies and Applications, 2024)
Environmentally benign pH-indicating wound dressing comprised of carbohydrates chitosan (CH) and pectin (P), and anthocyanin grape (AG) dye is created via layer-by-layer assembly. Cotton fabric coated with eight bilayers of (CH-AG)4/(P-AG)4 deposited 1.97 % AG-dye. It exhibited a visible and immediate color change from pink to violet-blue while increasing its pH value from 6 to pH 7, matching the turning pH point of healing into an infected wound. Color transition of AG-dye in water-based buffers, tested by VIS-spectroscopy, shows the same color change when the pH value increased from 6 to 7. This coating imparts excellent antimicrobial activity against Gram-positive bacteria Staphylococcus aureus and yeast Candida albicans, moderate antibacterial activity against Gram-negative Escherichia coli bacteria, and no cytotoxicity on human fibroblast cells (MRC-5). This research proposes a sustainable, low-cost, and simple method for obtaining smart wound dressing that provides real-time monitoring of the wound pH.